The Browser Hacker's Handbook - Alcorn, Wade (Wiley, 2014)
Hackers exploit browser vulnerabilities to attack deep within networks. The Browser Hacker's Handbook gives a practical understanding of hacking the everyday web browser and using it as a beachhead to launch further attacks deep into corporate networks. Written by a team of highly experienced computer security experts, the handbook provides hands-on tutorials exploring a range of current attack methods. The web browser has become the most popular and widely used computer "program" in the world. As the gateway to the Internet, it is part of the storefront to any business that operates online, but it is also one of the most vulnerable entry points of any system. With attacks on the rise, companies are increasingly employing browser-hardening techniques to protect the unique vulnerabilities inherent in all currently used browsers. The Browser Hacker's Handbook thoroughly covers complex security issues and explores relevant topics such as: Bypassing the Same Origin Policy; ARP spoofing, social engineering, and phishing to access browsers; DNS tunneling, attacking web applications, and proxying--all from the browser; Exploiting the browser and its ecosystem (plugins and extensions); Cross-origin attacks, including Inter-protocol Communication and Exploitation. The Browser Hacker's Handbook is written with a professional security engagement in mind. Leveraging browsers as pivot points into a target's network should form an integral component into any social engineering or red-team security assessment. This handbook provides a complete methodology to understand and structure your next browser penetration test.--